2013
DOI: 10.1371/journal.pone.0054221
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Target of Rapamycin (Mtor) Is Essential for Murine Embryonic Heart Development and Growth

Abstract: Mechanistic target of rapamycin (Mtor) is required for embryonic inner cell mass proliferation during early development. However, Mtor expression levels are very low in the mouse heart during embryogenesis. To determine if Mtor plays a role during mouse cardiac development, cardiomyocyte specific Mtor deletion was achieved using α myosin heavy chain (α-MHC) driven Cre recombinase. Initial mosaic expression of Cre between embryonic day (E) 10.5 and E11.5 eliminated a subset of cardiomyocytes with high Cre activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 28 publications
5
63
0
1
Order By: Relevance
“…Compared with controls, the oxidation of [2][3][4][5][6][7][8][9][10][11][12][13][14] C]pyruvate was 2-fold higher in Acsl1 T2/2 cardiac mitochondria, consistent with increased flux through the tricarboxylic acid cycle (Fig. 1H).…”
Section: Loss Of Cardiac Acsl1 Decreased the Use Of Fatty Acids And Imentioning
confidence: 72%
See 4 more Smart Citations
“…Compared with controls, the oxidation of [2][3][4][5][6][7][8][9][10][11][12][13][14] C]pyruvate was 2-fold higher in Acsl1 T2/2 cardiac mitochondria, consistent with increased flux through the tricarboxylic acid cycle (Fig. 1H).…”
Section: Loss Of Cardiac Acsl1 Decreased the Use Of Fatty Acids And Imentioning
confidence: 72%
“…In the heart, mTORC1 activation is required for growth; both global and cardiac-specific knockouts of mTOR are embryonic lethal (14,48). A temporal knockout of mTOR in adult heart demonstrated that mTOR is also needed for normal mitochondrial function, fatty acid oxidation, and heart contraction (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations